-2(3x+5)+4-7x=6x-18

Simple and best practice solution for -2(3x+5)+4-7x=6x-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3x+5)+4-7x=6x-18 equation:


Simplifying
-2(3x + 5) + 4 + -7x = 6x + -18

Reorder the terms:
-2(5 + 3x) + 4 + -7x = 6x + -18
(5 * -2 + 3x * -2) + 4 + -7x = 6x + -18
(-10 + -6x) + 4 + -7x = 6x + -18

Reorder the terms:
-10 + 4 + -6x + -7x = 6x + -18

Combine like terms: -10 + 4 = -6
-6 + -6x + -7x = 6x + -18

Combine like terms: -6x + -7x = -13x
-6 + -13x = 6x + -18

Reorder the terms:
-6 + -13x = -18 + 6x

Solving
-6 + -13x = -18 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-6 + -13x + -6x = -18 + 6x + -6x

Combine like terms: -13x + -6x = -19x
-6 + -19x = -18 + 6x + -6x

Combine like terms: 6x + -6x = 0
-6 + -19x = -18 + 0
-6 + -19x = -18

Add '6' to each side of the equation.
-6 + 6 + -19x = -18 + 6

Combine like terms: -6 + 6 = 0
0 + -19x = -18 + 6
-19x = -18 + 6

Combine like terms: -18 + 6 = -12
-19x = -12

Divide each side by '-19'.
x = 0.6315789474

Simplifying
x = 0.6315789474

See similar equations:

| (3P-4)=-25 | | 2.5x=100-2.5x | | 34five+23five= | | 15+9u-3=16+-2u-7 | | 4a^2-11a=3 | | -2/3w-8/15=-4/5 | | 15+9u-3=16-2u-7 | | tan^2x=0.25 | | 3y-27=-15 | | 13/48+x/2-(2x+1)/6=1 | | h=-16t^2+44t+7 | | 6+-2=y | | (x+14)(x+3)=0 | | -4k+2(5k-6)=-3k-30 | | -4(2x+4)=12x-8 | | 4x=6x-3 | | 3x+2x=85 | | 20-18=200 | | .003x-.2=.01 | | 15p+9-11-p=-2(2p+4)-3(2p-2) | | -4(7-2t)=4(t-1) | | 3y*2+3(4y*2-2)= | | y^2+10y=11 | | -5x-6(2x-2)=-107 | | -8(3x+12)-13=4x+10 | | 2x+9=4(x+6) | | 15x+11x+20=90 | | 5x-10=-7x-70 | | y-19=6 | | 3x+6(2x-3)=102 | | x-5+8x=-1 | | -17/9= |

Equations solver categories